The CHF/EUR exchange rate during the Swiss National Bank's minimum exchange rate policy: a latent likelihood approach. Issue 1 (2nd January 2019) - Hanke, M.; Poulsen, R.; Weissensteiner, A.
Abstract : Our model treating the rate bound in terms of a put option accurately predicts the CHF/EUR exchange rate following the removal of the lower bound of 1.20